The complete mitochondrial genome of pitted stingray Bathytoshia brevicaudata (Myliobatiformes: Dasyatoidea) - Jong-Oh Kim; Yong Bae Seo; Jiyoung Shin; Ji-Young Yang; Gun-Do Kim (Mitochondrial DNA. Part B. Resources, 2020)
The complete mitochondrial genome of pitted stingray, Bathytoshia brevicaudata (Myliobatiformes: Dasyatoidea) was investigated by next-generation sequencing. The analyzed mitochondrial genome was 17,640 nucleotides in length and had 59.2% for AT contents. This genome contains 2 ribosomal RNA genes, 13 protein-coding genes, 22 transfer RNA genes. and 1 putative control region. Five protein-coding genes (ATPase6, COII, ND2, ND3, ND4) including incomplete stop codons and four tRNAs have atypical codons. The phylogenetic inference including 13 species of the same family revealed a close relationship with Pteroplatytrygon violacea. This is the first mitochondrial genome report from genus Bathytoshia.